Penguatan Elemen Masyarakat Melalui Program Pelatihan Pengelolaan Sampah Sebagai Upaya Perubahan Perilaku Penggunaan Mck Di Desa Takofi Kecamatan Pulau Moti - Lita Asyriati Latif; Ahmad Seng; Muhammad Fadly Hi Abbas (Universitas Patria Artha, 2022)
The Effective waste management system can be started from the direction of sorting waste independently by each family. This socialization on how to sort waste will be essential in adding insight and providing inspiration for economic opportunities behind independent, group, networked and sustainable waste management. Through the PKM Program of the Faculty of Engineering in 2022, the Mechanical Engineering Study Program will carry out a program to strengthen community elements and waste management training to change the behavior of using MCK, which is currently getting worse for people in Takofi Village. The problems of the Takofi Village community about waste management are; pollution originating from MCK waste used by villagers, littering behavior by villagers, no reference to independent waste management models from the village government, and the absence of village youth organizations or groups in providing education about the proper use of MCK and waste disposal education. . The implementation of community service program activities regarding the Socialization of the Importance of Clean Water for STUNTING Prevention was attended by 20 consisting of fathers, mothers and the younger generation. The socialization was carried out by providing important material about waste management using the 3R method, namely reuse, recycle and reduce